Methylphenidate Dosing Schedules - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Efficacy and side effects of twice daily (bid) and three times daily (tid) methylphenidate (MPH) dosing schedules (mean dose, 8 mg, 0.3 mg/kg) in 25 boys with attention deficit hyperactivity disorder (ADHD) were compared in a 5-week, placebo-controlled, crossover evaluation at the Departments of Psychiatry and Pediatrics, University of Chicago.